Chronic Heart Failure in Rheumatoid Arthritis Patients (Part III): Effects of Antirheumatic Drugs - D. S. Novikova; H. V. Udachkina; I. G. Kirillova; T. V. Popkova (Столичная издательская компания, 2020)
Chronic autoimmune inflammation is one of the leading risk factors for the development of chronic heart failure (CHF) in rheumatoid arthritis (RA). The purpose of the review is to analyze the results of investigations on the effects of conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs), biological disease-modifying anti-rheumatic drugs (bDMARDs), and targeted csDMARDs on cardiac function and the risk of developing CHF in patients with RA. Methotrexate may reduce the CHF risk and have a positive effect on the course of this condition in patients with RA. Despite the data on the presence of leflunomide effects that impede myocardial remodeling, there is no evidence of the role of the drug in the prevention of CHF in RA patients. Hydroxychloroquine may contribute to the prevention of CHF, but the risk of developing severe cardiotoxicity should be considered when taking the drug for a long time. Most studies have not revealed the negative effect of tumor necrosis factor inhibitors on the prevalence and incidence of new cases of CHF in RA patients, and an improvement in the structure and function of the heart during therapy has been shown. Inhibitors of interleukin (IL) -1, inhibitors of IL-6, inhibitors of T-cell co-stimulation, anti-B-cell therapy, targeted csDMARDs do not increase the risk of CHF and may have cardioprotective effects, including slowing the progression of left ventricle myocardial dysfunction. Due to the high risk of CHF and CHF-associated mortality in RA patients, early diagnosis of cardiac dysfunction, development of a prevention and treatment strategies are needed, including high-quality prospective studies to assess the effect of anti-rheumatic therapy on myocardial function, risk of developing and decompensation of CHF in RA patients. It is possible that some drugs may possess protective effects on cardiomyocytes so they could become the first-line drugs in patients with CHF or the risk of its development.